Erythropoietin Pathway: A Potential Target for the Treatment of Depression - Ma, Chongyang (Int J Mol Sci, 2016)
During the past decade, accumulating evidence from both clinical and experimental studies has indicated that erythropoietin may have antidepressant effects. In addition to the kidney and liver, many organs have been identified as secretory tissues for erythropoietin, including the brain. Its receptor is expressed in cerebral and spinal cord neurons, the hypothalamus, hippocampus, neocortex, dorsal root ganglia, nerve axons, and Schwann cells. These findings may highlight new functions for erythropoietin, which was originally considered to play a crucial role in the progress of erythroid differentiation. Erythropoietin and its receptor signaling through JAK2 activate multiple downstream signaling pathways including STAT5, PI3K/Akt, NF-κB, and MAPK. These factors may play an important role in inflammation and neuroprogression in the nervous system. This is particularly true for the hippocampus, which is possibly related to learning, memory, neurocognitive deficits and mood alterations. Thus, the influence of erythropoietin on the downstream pathways known to be involved in the treatment of depression makes the erythropoietin-related pathway an attractive target for the development of new therapeutic approaches. Focusing on erythropoietin may help us understand the pathogenic mechanisms of depression and the molecular basis of its treatment.